Anxiety Disorders: Recent Global Approach to Neuro-pathogenesis, Drug Treatment, Cognitive Behavioral Therapy, and Their Implications (Bangladesh Journal of Medical Science, 2021)
Anxiety is a group of mental disorders characterized by the sudden feeling of intense fear, panic, shortness of breath, chest pain, restlessness, GIT problems, insomnia, fatigue, muscle tension, sweating, loss of memory, blurred vision, and impaired learning. It occurs typically in response to a stressful situation that may become pathological when it is no longer controlled or occurs in the absence of real threat. This review aimed to appraise the literature on the prevalence, classification, neuro-pathogenesis, diagnoses, and treatment of anxiety disorders (AD). The search was made using PubMed, Embase, MEDLINE, and PsycINFO databases. Anxiety disorders are the most common mental disorders affecting humans, especially among developing nations. In general, the lifetime prevalence of AD is about 14%, with an annual prevalence of 31%. Unfortunately, AD, in general, is underdiagnosed and undertreated globally.Bangladesh Journal of Medical Science Vol.20(3) 2021 p.487-503